1972
DOI: 10.1021/ja00761a034
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of phenylacetic acid and methyl phenylacetate in methanol

Abstract: of those estimated for the hydroxymercuration of olefinic compounds by other organomercurial ions from measurements on the rates of exchange of olefins with oxymercurials.9 Also pertinent to the present theme are recent direct observations of the acid-induced cleavage of diacetonylmercury10 and of the methoxymercuration of an aliene by organomercury(II) ions.11 Finally, the results of these studies yield information, not previously available, about the effects of the systematic variation of R in the series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Literature data on the absorbance of benzyl radical also confirms this assignment. [10][11][12][13][14] Assuming that S and L have been formed independently, the decay of the short-lived species contains components of all its deactivation processes, which are dimerization and hydrogen abstraction from the starting compound and from the solvent. Table 1 also shows an apparent decay constant for S, assuming monoexponential behavior.…”
Section: Laser Flash-photolysismentioning
confidence: 99%
“…Literature data on the absorbance of benzyl radical also confirms this assignment. [10][11][12][13][14] Assuming that S and L have been formed independently, the decay of the short-lived species contains components of all its deactivation processes, which are dimerization and hydrogen abstraction from the starting compound and from the solvent. Table 1 also shows an apparent decay constant for S, assuming monoexponential behavior.…”
Section: Laser Flash-photolysismentioning
confidence: 99%
“…In its simplest form, this reaction involves the cleavage of a carbon-carbon bond of carboxylic acids or, more commonly a carboxylate anion, forming carbon dioxide and leaving an organic residue which can be utilised in subsequent reactions. Among various carboxylic acids, much attention has been focused on the decarboxylation of arylacetic acids and their derivatives thermally [1][2][3][4][5][6][7][8][9][10][11][12][13] or photochemically [14][15][16][17][18][19][20][21] in the presence of various oxidants, sensitisers and electron acceptors. Such acids provide a benzylic moiety which stabilises an incipient radical or ionic intermediate after loss of carbon dioxide.…”
mentioning
confidence: 99%
“…17,18 Photolysis of phenylacetic acid, sodium phenylacetate, phenylacetate esters and benzyl esters have also been investigated. 19,20 However, in comparison with thermal decarboxylation, relatively little work has been reported on photochemical decarboxylation of carboxylic acids by metallic oxidants. 21,22 During our initial experimental studies on the eect of light-sensitive compounds of mercury on photolysis of arylcarboxylic acids we found that these acids are readily decarboxylated when treated with HgO under illumination in organic solvents.…”
mentioning
confidence: 99%
“…The peroxyl radical would ®nally give benzophenone 1b. 19,20,23 Therefore, the formation of these dimeric products is attributed to homocoupling of arylalkyl radicals via carbon± carbon bond formation. Evidence for the formation of the arylalkyl radical as an intermediate was obtained from oxygen-trapping experiments.…”
mentioning
confidence: 99%